Analysis of the effects of climate change on the gyre in Lake Biwa, Japan. Issue 2 (19th January 2023) - Koue, Jinichi; Shimadera, Hikari; Matsuo, Tomohito; Kondo, Akira
Abstract: The currents of gyre (circulation) flow play an important role in the transportation and mixing of dissolved or suspended nutrients and chemical substances. In recent years, climate change has affected the flow field in Lake Biwa. However, how much climate change can influence the flow field has not been clarified enough yet. In the present study, using a three-dimensional hydrodynamic model, we investigated the effect of changes in air temperature, wind speed, and precipitation on the change of the flow field in Lake Biwa. For sensitivity analysis, numerical simulations were performed for a baseline case using realistic meteorological data from 2007 to 2012, as well as hypothetical cases using meteorological data. The analysis revealed that the changes in air temperature and precipitation changed stratification and vorticity in the surface layer in each season. The strength of the stratification affected the gyre strength in the surface layer. The change in wind speed, on the other hand, changed the wind stress acting on the lake's surface, influencing the strength of gyre significantly. Increased wind speed lengthened the radius of the gyre in Lake Biwa, while decreased wind speed made it weaker above and below the thermocline. HIGHLIGHTS: The currents of gyre flow play an important role in the transportation and mixing of dissolved or suspended nutrients and chemical substances. The significant feature of the flow field in Lake Biwa, Japan is the system of several gyres formed in the surface layer of the lake. The change in wind speed altered the wind stress acting on the surface of the lake, which significantly influenced the strength of the gyre.